Censorship detected in EG (Egypt) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Egypt. Data sourced from OONI.
Censorship Incident ID: EG-2026-1578. Severity: critical. Confidence: 90%